2012
DOI: 10.2337/db11-1528
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cerebral but Not Peripheral Angiogenesis in the Goto-Kakizaki Model of Type 2 Diabetes Involves VEGF and Peroxynitrite Signaling

Abstract: We previously reported enhanced cerebrovascular remodeling and arteriogenesis in experimental type 2 diabetes. This study tested the hypotheses that 1) cerebral but not peripheral angiogenesis is increased in a spatial manner and 2) peroxynitrite orchestrates vascular endothelial growth factor (VEGF)-mediated brain angiogenesis in diabetes. Stereology of brain, eye, and skeletal muscle microvasculature was evaluated in control and diabetic rats using three-dimensional images. Migration and tube formation prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
107
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 48 publications
10
107
0
Order By: Relevance
“…Although there are many reports of enhanced neovascularization in type 2 diabetes (Li et al, 2010;Prakash et al, 2013;Prakash et al, 2012;Ye et al, 2011), our analysis of isolectin labeled vessels and proliferative cells (using Ki67 antibody) suggested that the increase in surface area in type 1 diabetic mice was more likely related to an increase in vessel diameter rather than sprouting of new vessels. However, there are limitations associated with Ki67 immunohistochemistry which labels proliferating cells within a relatively brief temporal window, thereby underestimating the total number of proliferating cells.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Although there are many reports of enhanced neovascularization in type 2 diabetes (Li et al, 2010;Prakash et al, 2013;Prakash et al, 2012;Ye et al, 2011), our analysis of isolectin labeled vessels and proliferative cells (using Ki67 antibody) suggested that the increase in surface area in type 1 diabetic mice was more likely related to an increase in vessel diameter rather than sprouting of new vessels. However, there are limitations associated with Ki67 immunohistochemistry which labels proliferating cells within a relatively brief temporal window, thereby underestimating the total number of proliferating cells.…”
Section: Discussionmentioning
confidence: 57%
“…Remarkably, restoring or enhancing VEGF signaling can improve learning and memory in healthy and brain injured animals (Cao et al, 2004;Ortuzar et al, 2013) and protect the brain from damage and dysfunction caused by stroke or ALS (Jin et al, 2000;Storkebaum et al, 2005;Zhang and Chopp, 2009). Despite increasing evidence that diabetes leads to abnormal VEGF signaling and pathogenic vessel remodeling (Caldwell et al, 2005;Prakash et al, 2012;Reeson et al, 2015), no study has explored whether manipulating VEGF signaling in an animal model of diabetes could have therapeutic value in preventing pathological changes to cognition. In the present study, we discovered that uncontrolled diabetes leads to a selective reduction of VEGF and VEGF-R2 expression in the hippocampus, as well as downstream effectors of VEGF signaling such as pAKT.…”
Section: Introductionmentioning
confidence: 99%
“…16 The experimental results revealed a significant rise in the level of vascular endothelial growth factor (VEGF) and nitrotyrosine. 24 The levels of growth factors and cytokines that were regarded as important in the development of sprouting collateral vessels from the extracranial vascular system by indirect revascularization, such as the expression of VEGF, basic fibroblast growth factor, transforming growth factorb, granulocyte colony-stimulating factor, and hepatocyte growth factor, have been proven to be elevated in many studies in MMD patients. 35 Therefore, we propose the following hypothesis: the expression of growth factors and cytokines described above might be higher in MMD patients complicated with T2DM than in MMD patients without T2DM.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…79 Diabetic rats have less pericytes along microvessels of the brain and increased cerebral angiogenesis. 31 However, whether the loss of pericytes gives way to angiogenesis or Figure 3. Redox window and angiogenesis.…”
Section: Diabetes and Neovascularizationmentioning
confidence: 99%